1996
DOI: 10.1152/jn.1996.76.6.3850
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response characteristics of the hearing organ in the low-frequency regions of the cochlea

Abstract: 1. With the use of an in vitro preparation of the guinea pig temporal bone, in which the apical turns of the cochlea are exposed, the mechanical and electrical responses of the cochlea in the low-frequency regions were studied during sound stimulation. 2. The mechanical characteristics were investigated in the fourth and third turns of the cochlea with the use of laser heterodyne interferometry, which allows the vibratory responses of both sensory and supporting cells to be recorded. The electrical responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 0 publications
5
41
0
1
Order By: Relevance
“…Frequency tuning may, therefore, be less sharp and response amplitudes lower than is the case in vivo. Previous studies, and data obtained with the current technique, showed that mechanical frequency-tuning curves obtained in this preparation (20) are similar to inner hair cell receptor-potential tuning curves measured from the same cochlear region in vivo at 50-70 dB SPL (21). At these stimulus levels, the response of the hearing organ begins to be dominated by passive mechanics.…”
Section: Discussionsupporting
confidence: 79%
“…Frequency tuning may, therefore, be less sharp and response amplitudes lower than is the case in vivo. Previous studies, and data obtained with the current technique, showed that mechanical frequency-tuning curves obtained in this preparation (20) are similar to inner hair cell receptor-potential tuning curves measured from the same cochlear region in vivo at 50-70 dB SPL (21). At these stimulus levels, the response of the hearing organ begins to be dominated by passive mechanics.…”
Section: Discussionsupporting
confidence: 79%
“…The increase was approximately 25% and is similar to reported values [20]. Current injections revealed fundamental differences between the individual OHC rows.…”
Section: Current Affects Sound-evoked Rl Vibrationssupporting
confidence: 89%
“…Previous studies on this in vitro preparation showed that the opening in the bone, which is necessary to gain optical access to the sensory cells, leads to frequency tuning curves that are sharper than those frequency tuning curves likely to be observed in vivo (27). This effect occurs because the opening creates a pressure release pathway, which reduces the effective stimulus level at frequencies below 300 Hz (the opening is expected to influence current-evoked motion relatively less than stapes-evoked motion).…”
Section: Significancementioning
confidence: 89%